2010
DOI: 10.1016/s0929-6646(10)60060-5
|View full text |Cite
|
Sign up to set email alerts
|

Decreased GRP78 Protein Expression is a Potential Prognostic Marker of Oral Squamous Cell Carcinoma in Taiwan

Abstract: GRP78 protein is a possible biomarker of oral cancer in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 21 publications
0
36
0
1
Order By: Relevance
“…The OCSL cells showed greater proliferation, horizontal and vertical migration, and transwell invasion abilities in comparison with OC2 cells [32]. In this study, we demonstrated that reversine suppressed the growth of these two OSCC cells.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The OCSL cells showed greater proliferation, horizontal and vertical migration, and transwell invasion abilities in comparison with OC2 cells [32]. In this study, we demonstrated that reversine suppressed the growth of these two OSCC cells.…”
Section: Discussionmentioning
confidence: 54%
“…Especially, the apoptosis percentage was over fifty in OCSL cells after 24 hours treatment. (Figure 3B), highly suggesting that reversine was more effective in OCSL cells, the cell line previously proven more malignant than OC2 [32]. …”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Fadu, a hypopharynx squamous cell carcinoma cell line, and 2 oral cancer cell lines, OC2 and OCSL, two oral squamous cell carcinoma cell lines derived from two Taiwanese men with habits of drinking, smoking, and areca nut chewing [33], were maintained in RPMI medium supplemented with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin. The oral cancer cell lines SCC4 and SCC25, two tongue squamous cell carcinoma cell lines, were maintained in DMEM/F12 with similar supplements.…”
Section: Methodsmentioning
confidence: 99%
“…99 GRP78 is overexpressed in 76% of breast cancers, and in lung, gastric and hepato cellular tumors, but downregulated in oral squamous-cell cancers. [100][101][102][103][104] In addition to its role within the endo plasmic reticulum, GRP78 has been found on the surface of prostate cancer cells. 105 Although the exact role of GRP78 in cancer cells remains elusive, it prevents apoptosis by binding and inhibiting caspase 7 and suppressing the pro apoptotic proteins BIK and BAX and mitochondrial release of cytochrome c. 106,107 Introduction of GRP78 confers drug resistance in cancer cells, which are resensitized to cytotoxic chemotherapy when it is removed.…”
Section: Deregulated Global Control and Cancermentioning
confidence: 99%